1988
DOI: 10.1007/bf00196067
|View full text |Cite
|
Sign up to set email alerts
|

Water levels in Lake Ontario 4230?2000 years B.P.: evidence from Grenadier Pond, Toronto, Canada

Abstract: Lake Ontario water levels have been rising for the past 11 500 years due to differential isostatic rebound of the St. Lawrence outlet. Small scale fluctuations in water level superimposed on this general trend have received little study, with the exception of the 'Nipissing Flood'.The transgression of a Grenadier Pond was studied from cores along a transect from the bar that separates the pond from Lake Ontario to the marsh on the north shore. Radiocarbon dates of the transition from swamp peat to pond marl in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Because of its proximity (1 13 km) to the controlling sill at Galop Rapids, it has experienced a slower rate of water-level rise than the lagoons studied by Flint et al (1988) and McCarthy and McAndrews (1988) (Fig. As a result, it is expected that the small fluctuations (*I m) in water level proposed by Flint et al (1988) and McCarthy and McAndrews (1988) would be more clearly recorded in the lagoon stratigraphy. The rate of sediment accumulation (see below) has also been much lower and water depths have remained shallower (<I m prior to 1500 BP) here than in the previously studied areas.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Because of its proximity (1 13 km) to the controlling sill at Galop Rapids, it has experienced a slower rate of water-level rise than the lagoons studied by Flint et al (1988) and McCarthy and McAndrews (1988) (Fig. As a result, it is expected that the small fluctuations (*I m) in water level proposed by Flint et al (1988) and McCarthy and McAndrews (1988) would be more clearly recorded in the lagoon stratigraphy. The rate of sediment accumulation (see below) has also been much lower and water depths have remained shallower (<I m prior to 1500 BP) here than in the previously studied areas.…”
Section: Introductionmentioning
confidence: 88%
“…I). The purpose of this study is, therefore, to critically test the ideas proposed by Flint et al (1988,1989) and McCarthy and Methods McAndrews (1988), which are based on studies at the west end Eight cores with lengths of 0.8-2.4 m were collected from the open-water lagoon in 1987 and 1988 (Fig. As a result, it is expected that the small fluctuations (*I m) in water level proposed by Flint et al (1988) and McCarthy and McAndrews (1988) would be more clearly recorded in the lagoon stratigraphy.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Overall the level of Lake Ontario has risen since 11 500 years BP when the lake was formed in postglacial times (McCarthy and McAndrews 1988). However, there is much evidence for fluctuation superimposed on this general trend.…”
Section: Likelihood Of Forest Burialmentioning
confidence: 99%
“…However, there is much evidence for fluctuation superimposed on this general trend. Fluc tuation occurred in the early postglacial time (Jackson et al 2000), and, much later (3000-2100 years BP), there were also periods of rapid rise in water level related to episodes of relatively cool, wet climate (McCarthy and McAndrews 1988). Also superimposed on the general rising trend, Flint et al (1988) reported oscillations over the past 3300 years, with an amplitude in the order of 1 m over several hundred years.…”
Section: Likelihood Of Forest Burialmentioning
confidence: 99%